Burden of dry eye disease in Germany: a retrospective observational study using German claims data. Issue 4 (17th November 2019) - Siffel, Csaba; Hennies, Nora; Joseph, Corey; Lascano, Valeria; Horvat, Pia; Scheider, Maria; Ganzera, Frank
Abstract: Purpose: To evaluate the clinical and economic burden of dry eye disease (DED) among affected patients in Germany. Methods: Adult patients (≥18 years) with ≥1 confirmed diagnosis of DED during the study period (2008–2015) were identified from the medical claims of ~3.6 million insured patients from Betriebskrankenkassen, a German statutory health insurance database. Prevalence (per 1000 patients) and incidence (per 1000 person‐years at risk) were estimated, and demographic and clinical characteristics, treatment history (excluding over‐the‐counter tear supplements), healthcare resource use (HCRU) and costs were assessed. Results: In this population, the prevalence of DED increased from 20.24 in 2008 to 23.13 per 1000 patients in 2014. Overall incidence was 6.24 per 1000 person‐years at risk (2008–2015). Prevalence and incidence increased with age and were higher in women. Mean age at index was 63.4 years (incident cohort, n  =   35 026). The most common ocular comorbidity was cataract (48.5%), and ~36% of patients were dispensed a reimbursed DED‐specific medication during the postindex period – most commonly, corticosteroids alone (13.2%) or in combination with anti‐infectives (21.8%). HCRU was high in patients with DED, mostly due to comorbidities. HCRU and associated costs were highest in patients ≥60 years. Total costs during the postindex period were higher in the DED cohort than among matched controls (€117 million versus €107 million; p < 0.001). Conclusion: This retrospective database analysis provides a better understanding of the epidemiology, clinical characteristics, real‐world treatment patterns, HCRU and costs associated with DED in patients living in Germany.